The effect of donor–recipient sex matches on lung transplant survival: An analysis of the United Network for Organ Sharing databaseCentral MessagePerspective - Elizabeth Profozich, BS; Abul Kashem, MD, PhD; Roh Yanagida, MD, PhD; Manish Suryapalam, BS; Ke Cheng, PhD; Hiromu Kehara, MD, PhD; Norihisa Shigemura, MD, PhD; Yoshiya Toyoda, MD, PhD (JTCVS Open, 2024)
Objective: To investigate the impact of donor–recipient (DR) sex matches on survival after lung transplantation while controlling for size difference in the United Network of Organ Sharing (UNOS) database. Methods: We performed a retrospective study of 27,423 lung transplant recipients who were reported in the UNOS database (January 2005-March 2020). Patients were divided into groups based on their respective DR sex match: male to male (MM), male to female (MF), female to female, (FF), and female to male (FM). Kaplan–Meier curve and Cox regression with log-rank tests were used to assess 1-, 3-, 5-, and 10-year survival. We also modeled survival for each group after controlling for size-related variables via the Cox regression. Results: Kaplan–Meier curves showed overall significance at 1-, 3-, 5-, and 10-year end points (P < .0001). Estimated median survival time based on Kaplan–Meier analysis were 6.41 ± 0.15, 6.13 ± 0.18, 5.86 ± 0.10, and 5.37 ± 0.17 years for FF, MF, MM, and FM, respectively (P < .0001). After we controlled for size differences, FF had statistically significantly longer 5- and 10-year survival than all other cohorts. MF also had statistically significantly longer 5- and 10-year survival than FM. Conclusions: When variables associated with size were controlled for, FF had improved survival than other DR groups. A female recipient may experience longer survival with a female donor’s lungs versus a male donor’s lungs of similar size.